2020
DOI: 10.5765/jkacap.190030
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Korean Practice Parameter for Adult Attention-Deficit/Hyperactivity Disorder

Abstract: Objectives: Adult attention-deficit/hyperactivity disorder (ADHD) is an important mental health problem that needs resolution, especially considering the high rates of ADHD continuation from childhood to adolescence/adulthood and the high prevalence of ADHD in adults. Adults with ADHD have lifelong negative impacts and require close monitoring with long-term follow-up. Hence, the establishment of a Korean practice parameter for adult ADHD is necessary to minimize discontinuation of treatment and enable informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 236 publications
(223 reference statements)
0
13
0
Order By: Relevance
“…The prevalence of ADHD (F90) was notably low. In this study, the reason that the occurrence of ADHD rapidly declined in adulthood may be partly because ADHD medications are not covered by Korea's national health insurance system for people aged 19 years or older, which might have contributed to diminished treatment adherence because of the burden of treatment costs [19]. However, in 2016, this problem was resolved by expanding the coverage for adults, and as the combined prescription of ADHD medications has been permitted in December 2019, the number of ADHD diagnoses may increase in the coming years [19].…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of ADHD (F90) was notably low. In this study, the reason that the occurrence of ADHD rapidly declined in adulthood may be partly because ADHD medications are not covered by Korea's national health insurance system for people aged 19 years or older, which might have contributed to diminished treatment adherence because of the burden of treatment costs [19]. However, in 2016, this problem was resolved by expanding the coverage for adults, and as the combined prescription of ADHD medications has been permitted in December 2019, the number of ADHD diagnoses may increase in the coming years [19].…”
Section: Discussionmentioning
confidence: 93%
“…ADHD is often associated with a higher rate of psychiatric comorbidity in both children and adults than in the general population. 28 Between 65 and 89% of all adults with ADHD suffer from one or more psychiatric disorders during their lifespan. 29 The subjects of this study also had 1.66 comorbid psychiatric disorders per person.…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies cannot be found in the literature, which limits the interpretation of our results. Moreover, polypharmacy including ADHD drugs, is frequently prescribed for adult ADHD patients due to comorbid psychiatric and medical conditions [ 3 ]. Therefore, it is difficult to evaluate only the effects of ADHD drugs and only the effects in the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable variation in the persistence rate of attention-deficit/hyperactivity disorder (ADHD) from childhood to adulthood, with estimates ranging from 15% [ 1 ] to 27.8% [ 2 ], depending on the definition of ADHD. It is more difficult to diagnose ADHD in adults than in children and adolescents due to the high prevalence of other physical and mental disorders [ 3 ]. Therefore, newer and more reliable biological diagnostic methods are urgently needed to confirm the diagnosis of ADHD, especially in adults.…”
Section: Introductionmentioning
confidence: 99%